Technological entrepreneurship : technology-driven vs market-driven innovation - Chaston, Ian (Palgrave Macmillan, 2017)
This comprehensive book responds to the growing demand to study entrepreneurship as a key driver of innovation and competitive advantage. Challenging the existing idea that technological entrepreneurship exists predominantly in SMEs and as a result of market demands, the author argues that a commitment to entrepreneurship remains the most effective strategy for sustaining wealth generation for both organisations and entire nations. The aim of Technological Entrepreneurship is to provide the reader with additional knowledge and understanding of the concepts associated with the exploitation of technological entrepreneurship, and to demonstrate how associated management principles are somewhat different to those utilised in market-driven entrepreneurship. Validation of presented theoretical concepts is achieved through coverage of processes and practices utilised by real world organisations seeking to achieve maximum wealth generation, with specific emphasis on how technological entrepreneurship is the source of disruptive innovation within service sector organisations and how the philosophy is causing fundamental change in the provision of healthcare.
Keywords: Business.; Entrepreneurship.; Leadership.; Management.; Industrial management.; Technological innovations -- Economic aspects.; elektronické knihy; electronic books